3D numerical investigation of the effect of wall penetration depth on excavations behavior in sand. (June 2018) - Bahrami, Mohammad; Khodakarami, Mohammad Iman; Haddad, Abdolhosein
Abstract: The present paper evaluates the effect of penetration depth of a diaphragm wall on the behavior of excavations in sandy soils using the finite difference method. A three-dimensional (3D) modeling is performed for excavation depths of 10 to 20 m. The analysis reveals the safe values of penetration depth for designing a diaphragm wall. Furthermore, the evaluations undertaken in the present paper indicate that the two-dimensional (2D) modeling to depths of 10 m is associated with large errors. In addition, the evaluation of the validity of the traditional method for the design of a steel strut has been discussed.